PENGARUH GAYA KEPEMIMPINAN TRANSFORMATIONAL DAN KOMUNIKASI TERHADAP MOTIVASI DAN DAMPAKNYA PADA KINERJA KARYAWAN PT. XYZ - Andres Dharma Nurhalim (STIE Wiyatamandala, 2020)
PT. XYZ is a company engaged in the sale of paper and printing machines which will increase greatly in paper demand is increasing every year. therefore the employee's performance is an important factor in increasing the sales of the company so that it can compete with other competitors. To maintain the necessary motivation employee performance so employees can work maximal.This purpose of study was to analyze the effect of transformational leadership style, communication on the motivation and impact on employee performance PT. XYZ. The population used in this study were all employees of PT. XYZ, Tangerang Cipondoh many as 43 people. The analysis technique used is the path analysis (path analysis) .Data obtained from questionnaires distributed to all employees PT. XYZ totaling 43 people to measure transformational leadership style, communication on the motivation and performance of employees by using a Likert scale. From the analysis of the data obtained showed that the Transformational leadership style, communication to motivation and significant influence simultaneously on employee performance.